An orbital angular momentum acoustic metasurface for underwater defect detection; Applied Physics Express; Vol. 15, iss. 2 - Ma Qiujun; Lu Chunyao; Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich; Wang Kangyu; Wu Dawei (2022, 2022)
Title screen